Pharmacokinetic Consideration to Formulate Sustained Release Drugs: Understanding the Controlled Drug Diffusion through the Body Compartment of the Systemic Circulation and Tissue Medium-A Caputo Model (Baghdad Science Journal, 2023)
The aim of this study is to provide an overview of various models to study drug diffusion for a sustained period into and within the human body. Emphasized the mathematical compartment models using fractional derivative (Caputo model) approach to investigate the change in sustained drug concentration in different compartments of the human body system through the oral route or the intravenous route. Law of mass action, first-order kinetics, and Fick's perfusion principle were used to develop mathematical compartment models representing sustained drug diffusion throughout the human body. To adequately predict the sustained drug diffusion into various compartments of the human body, consider fractional derivative (Caputo model) to investigate the rate of concentration changing depending upon the change in the order of fractional differentiation in all the possible compartments of the body, i.e., systemic circulation and tissue compartments. Also, assigned a numerical parameter value to the rate of drug flow in different compartments to estimate the drug concentration. Results were calculated and figures were depicted by using MATLAB software (version R2020a). Illustrated graphical effects of change in concentration rate by assuming various intermediate values according to the fractional derivative (Caputo model). The resultant graphical representation concludes that considering the order of the differential equation values, the drug concentration varies depending upon its rate of constants in compartments concerning time. Considering the initial case for rough estimation where the body is indicated as a whole compartment, following division of the body into two model compartments. Whereas, the model I represents stomach, liver, and systemic blood, and model II consider arterial blood, liver tissue, and venous blood.